György Ligeti: Music of the Imagination - Steinitz, Richard (London Faber & Faber, 2003)
One of the world's best known living composers, Gyoergy Sandor Ligeti is widely acknowledged as the most influential and admired creative figure of the late twentieth century. His brilliantly conceived and challenging pieces, searingly intense at times and full of humor and irony at others, include the orchestral Apparitions and Atmospheres, piano etudes, the opera Le Grand Macabre, and the unaccompanied choral work Lux aeterna, which Stanly Kubrick actually pirated for the film soundtrack of 2001: A Space Odyssey.In this book, Richard Steinitz fuses biographical, stylistic, and technical analysis to examine thoroughly the evolution of Ligeti's innovative music. Drawing extensively on his own private conversations with the composer as well as on many published and recorded interviews, Steinitz places Ligeti's extraordinary body of work within the context of his complex personal life.
Keywords: Ligeti, György -- 1923-2006; 20th Century (1901-2000); Composer; Biography; Musical analysis; Hungary